Evaluation of Traffic Performance on Z.A. Pagar Alam Street After Underpass Road In Bandar Lampung Exists - Septriandini, Mutia; Sulistyorini, Rahayu; Purba, Aleksander (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
Jammed occurs due to the road infrastructure services level which is smaller than traffic movement needs that available. And the road which potentially to congest is ZA Pagar Alam street. So the government had made a solution to decrease the traffic jam by built an underpass on ZA Pagar Alam street. Furthermore, considering the need for underpass construction aims to reduce jam that occurs, so the writer bring out a research topic that is analyzing traffic flow after the underpass was built and comparing with the traffic flow before the underpass was built. The analysis of this road section performance using the 2014 Indonesian Road Capacity Guidelines method.It is known that the degree of saturation has decreased from 2013 by 1.00. It became 0.655 in 2016 and still dropped in 2019 to 0.63. But, from 2016 to 2019 the decrease was not significant. The speed in 2016 was 42.1 km / hour, and in 2019 was 41 km / hour. From the speed data, the results are not appropriate to RSNI T-14 2004 whereas the speed standard for urban roads should be 50-80 km / hour. So, it can be concluded from the comparison research of before and after the underpass was built, the construction of underpass on the section of ZA Pagar Alam street is not effective to decrease traffic jam.Keywords: Road Section, Degree of Saturation, Underpass